2014
DOI: 10.1166/jnn.2014.9053
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Water Contaminants by Iron Oxide Nanomaterials

Abstract: In recent years, there has been increasing concern about the usage of a broad range of organic substances, heavy metals and aromatic compounds in the aquatic environment due to their wide distribution and potential adverse health effects. The presence of toxic contaminants in water effluent, even at very low concentrations, is extremely harmful and undesirable. Various treatment processes have been investigated to reduce these toxic pollutants from wastewater. Because of the chemical stability of the contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Both phases have found important technical applications in everyday life, from ferrofluids and magnetic oils [14,15] and battery components [16], through to their large-scale use in water treatment plants [17,18]. In their fine particle form they have also attracted a great deal of recent interest in biomedical applications ranging from magnetic actuation for drug delivery, magnetic hyperthermia treatments for brain and prostate cancers, and novel medical imaging agents [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Both phases have found important technical applications in everyday life, from ferrofluids and magnetic oils [14,15] and battery components [16], through to their large-scale use in water treatment plants [17,18]. In their fine particle form they have also attracted a great deal of recent interest in biomedical applications ranging from magnetic actuation for drug delivery, magnetic hyperthermia treatments for brain and prostate cancers, and novel medical imaging agents [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…used nanoscale zero‐valent iron to remove tetracyclone from aqueous solution . In recent years, other studies have reported that iron oxide nanoparticles are very effective for removal of colour, heavy metals and aromatic compounds …”
Section: Introductionmentioning
confidence: 99%
“…[17] In recent years, other studies have reported that iron oxide nanoparticles are very effective for removal of colour, heavy metals and aromatic compounds. [18] In the study reported here, starch was used to modify and stabilize Fe 0 nanoparticles. The synthesized nanoparticles were characterized using various techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recently, the Fe 2 O 3 , one of the important metal oxide materials has received a considerable attention due to its narrow band gap, bio-compatibility, thermodynamically stable nature and environmental friendly, low-synthesis cost and so on [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%